Предмет: Алгебра,
автор: dimtarg
Упростить выражение:
(a-1)^2-(a+1)(a-2)
Ответы
Автор ответа:
0
1) ( а - 1 )^2 = а^2 - 2а + 1
2) ( а + 1 )( а - 2 ) = а^2 - 2а + а - 2 = а^2 - а - 2
3) а^2 - 2а + 1 - ( а^2 - а - 2 ) = а^2 - 2а + 1 - а^2 + а + 2 = - а + 3
2) ( а + 1 )( а - 2 ) = а^2 - 2а + а - 2 = а^2 - а - 2
3) а^2 - 2а + 1 - ( а^2 - а - 2 ) = а^2 - 2а + 1 - а^2 + а + 2 = - а + 3
Похожие вопросы
Предмет: Русский язык,
автор: mashasa72
Предмет: Биология,
автор: CharaCat
Предмет: Українська мова,
автор: DeathHunter228
Предмет: Математика,
автор: школьник201509